Semantic and Pragmatic Linguistic Aspects in Translation - ahyar, Juni; Ibrahim, Mohd Yusri; Muzir, Muzir (CV. Publikasi Indonesia, 2023)
Research language deployed translation issues, mainly concerning from linguistic, semantic and pragmatic aspects. Discussion was started by stating the importance of linguistic aspects comprehended and applied by a translator, such as grammar, phonology, morphology, syntax, semantics, pragmatics, sociolinguistics, and psycholinguistics. Research presented six meaning problems in translation, those related to lexical meaning, grammatical meaning, contextual meaning or situational meaning, textual meaning, sociocultural meaning, and idiomatic meaning. It can be concluded that the ability to apply linguistic aspect both from the source and targeted languages take important role to produce a good translation